A method for functional evaluation of caspase activation pathways in intact lymphoid cells using electroporation-mediated protein delivery and flow cytometric analysis - (:unkn) unknown (ELSEVIER SCIENCE BV, 2003)
The purpose of the study was to develop. a rapid technique for determining the functional status of caspase activation pathways in intact lymphocytes. Proteins known to activate caspase-family cell death proteases (cytochrome c; granzyme-B; caspase-8) were introduced into human leukemia and lymphoma cell lines, as well as freshly isolated lymphocytes and leukemia cells, by electroporation. Fluorochrome-labeled proteins with a wide range of molecular weights (from 15 to 150 kDa) were used to evaluate electroporation efficiency by flow cytometry and to compare the efficiency of protein delivery using various electroporation conditions. Caspase activity was monitored using a cleavable, cell-permeable fluorogenic substrate. Conditions were identified for efficient delivery of proteins of + 150 kDa into lymphoid cells. Caspase activation induced by various proteins was compared in normal and leukemic lymphocytic cells, revealing impaired caspase activation pathways in some malignant cells. We conclude that electroporation of apoptotic proteins into intact lymphoid cells can be used to contrast the status of various caspase activation pathways, thereby providing insights into the pathological defects in apoptosis regulation that exist in individual patient specimens. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: apoptosis; caspase; electroporation; flow cytometry; MAMMALIAN-CELLS; GRANZYME-B; APOPTOSIS; EXPRESSION; FAMILY